Transoral laser microsurgery for supraglottic carcinomas: results of a prospective multicenter trial (SUPRATOL) - Ambrosch, Petra; Meuret, Sylvia; Dietz, Andreas; Fazel, Asita; Fietkau, Rainer; Tostmann, Ralf; Schroeder, Ursula; Lammert, Anne; Künzel, Julian; Jäckel, Martin C.; Boeger, Daniel; Scherl, Claudia; et al. (Frontiers in Oncology, 2024)
BackgroundA limited number of single institutions have published retrospective cohort studies on transoral laser microsurgery for supraglottic laryngectomy (TLM-SGL). These studies have shown that the oncologic outcomes of TLM-SGL are comparable to those of open SGL. However, there is limited information available regarding swallowing rehabilitation and quality of life (QoL).Patients and methodsSUPRATOL is a prospective, multicenter trial assessing the functional outcomes of TLM-SGL +/− adjuvant radio-(chemo)-therapy. The primary endpoint was aspiration-free swallowing at 12 months, as established using fibreoptic endoscopic evaluation of swallowing (FEES) and defined as a grade < 6 on the penetration–aspiration scale. Secondary endpoints were swallowing- and voice-related QoL, the prevalence of temporary and permanent tracheostomy and percutaneous gastrostomy, local control, laryngectomy-free survival, overall survival, and disease-free survival, as well as the influence of treatment centers on outcomes.ResultsFrom April 2015 to February 2018, 102 patients were recruited from 26 German Otorhinolaryngology (ORL) hospitals. All patients had TLM-SGL and 96.1% underwent uni- or bilateral, mostly selective neck dissection. To 47.0% of patients, adjuvant radio-(chemo)-therapy (R(C)T) was administered. The median follow-up period was 24.1 months. At 12-month follow-up, completed by 84.3% of patients, 98.2%, 95.5%, and 98.8% were free of aspiration when tested with saliva, liquid, or pulp. Adjuvant R(C)T, pT category, and type of resection had no significant influence on swallowing rehabilitation. A total of 40.2% of patients had been tracheotomized, and in 46.1% of patients, a PEG tube was inserted. At the 24-month follow-up, 5.3% of patients still required a tracheostomy, and 8.0% continued to use a percutaneous endoscopic gastrostomy (PEG) tube. Deterioration of swallowing- and voice-related QoL was observed immediately after treatment, but patients recovered, and baseline values were reached again. The Kaplan–Meier 2-year rates for local control, laryngectomy-free survival, overall survival, and disease-free survival were 88%, 92%, 93%, and 82%, respectively.ConclusionsOur prospective multicenter trial shows that, at 12 months post-TLM-SGL +/− R(C)T, 95.5%–98.8% of patients achieved aspiration-free swallowing. Morbidity was higher than previously reported. The rates of permanent tracheostomy and gastrostomy tube placement correspond to previous cohort studies. The 2-year oncologic outcomes are within the reported range.Clinical trial registrationhttps://drks.de/search/en/trial/DRKS00004641, identifier (DRKS00004641).